2011
DOI: 10.1111/j.1742-4658.2011.08444.x
|View full text |Cite
|
Sign up to set email alerts
|

Engineering botulinum neurotoxin domains for activation by toxin light chain

Abstract: Targeted secretion inhibitors (TSI) are a new class of biopharmaceuticals designed from a botulinum neurotoxin protein scaffold. The backbone consists of the 50-kDa endopeptidase light chain and translocation domain (N-terminal portion of the heavy chain), lacks neuronal toxicity, but retains the ability to target cytoplasmic soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) proteins. TSI are produced as single-chain proteins and then cleaved post-translationally to generate functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Proteins of choices have been tethered to enzymatically inactive BoNT and demonstrated to translocate and function within the neuronal cell (Bade et al, 2004). While these studies have limited themselves to modulation of the enzymatic domain, replacement of the neuronal targeting receptor binding domain with one that recognizes a unique cellular surface protein could make BoNT an attractive delivery system for fold permissive cargo proteins to the scientist's target tissue of choice (Edupuganti et al, 2012; Stancombe et al, 2012). …”
Section: Productive Intoxication Requires Several Steps Of Interdomentioning
confidence: 99%
“…Proteins of choices have been tethered to enzymatically inactive BoNT and demonstrated to translocate and function within the neuronal cell (Bade et al, 2004). While these studies have limited themselves to modulation of the enzymatic domain, replacement of the neuronal targeting receptor binding domain with one that recognizes a unique cellular surface protein could make BoNT an attractive delivery system for fold permissive cargo proteins to the scientist's target tissue of choice (Edupuganti et al, 2012; Stancombe et al, 2012). …”
Section: Productive Intoxication Requires Several Steps Of Interdomentioning
confidence: 99%
“…In this fashion the range of BoNT therapeutic potential can be extended to non-neuronal cells as well, in particular secretory cells and sensory neurons [7273]. Additionally, engineered chimeric BoNT toxins, where domains displaying selective properties are swapped among the BoNT serotypes, are being developed as anti-nociceptive therapeutics to treat chronic pain and other secretory disorders [50].…”
Section: Toxin-based Therapeuticsmentioning
confidence: 99%
“…It has been shown that a single mutation (E244Q) in the active site of BoNT/A still cleaves SNAP25, whereas a double mutant (E224Q/Y366F) is catalytically inactive and forms a stable complex with SNAP25(141–204) peptide substrate [131]. Additional enzymatically inactive BoNTs have been reported, including BoNT/A RYM (R363A/Y365F) [132], ci-BoNT/A1 (H223A/E224A/H227A) [133], BoTIM/B (E231A/H234Y) [109], LH N /A (E224Q and H227Y) [73], and TeTIM (E234A) [134]. All these inactive mutants could have dual use for both developing vaccines as well as cargo-delivery platforms.…”
Section: Rational Approaches To Anti-bont Cargo-delivery Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins of choices have been tethered to enzymatically inactive BoNT and demonstrated to translocate and function within the neuronal cell (Bade et al, 2004). While these studies have limited themselves to modulation of the enzymatic domain, replacement of the neuronal targeting receptor binding domain with one that recognizes a unique cellular surface protein could make BoNT an attractive delivery system for fold permissive cargo proteins to the scientist's target tissue of choice (Edupuganti et al, 2012;Stancombe et al, 2012 A -BoNT/A HC (Fischer and Montal, 2006), B -TD (Fischer et al, 2008), and C -BTD (Fischer et al, 2012) A -BoNT/A TD and B -BTD channel activity is independent of a pH gradient across the membrane. Top panels illustrate representative channel activity monitored with pH 5 cis/7 trans, middle panel shows pH 6/7 and bottom panel shows no pH, symmetric pH 7, all measured at an applied voltage of −100 mV.…”
Section: Productive Intoxication Requires Several Steps Of Interdomaimentioning
confidence: 99%